2017
DOI: 10.1111/bph.14072
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 4 channel regulates vascular endothelial permeability during colonic inflammation in dextran sulphate sodium‐induced murine colitis

Abstract: These findings indicate that an up-regulation of TRPV4 channels in vascular endothelial cells contributes to the progression of colonic inflammation by increasing vascular permeability. Thus, TRPV4 is an attractive target for the treatment of inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 59 publications
4
47
0
Order By: Relevance
“…D'Aldebert et al (73) indicated the upregulated colonic TRPV4 expression in DSS-treated mice. Intracolonic administration of the TRPV4 agonists (4alphaphorbol-12,13-didecanoate or GSK1016790A) in mice activated NF-κB and activator protein 1 (AP-1) signaling pathway, resulting in exacerbated DSS-induced colitis and even transiently increased the paracellular permeability of epithelium and blood vessel, while TRPV4-knockout mice conferred a strong resistance to the colitis (73,81). These results prove the deleterious effects of TRPV4 on mucosal inflammation.…”
Section: Trpv4mentioning
confidence: 75%
See 1 more Smart Citation
“…D'Aldebert et al (73) indicated the upregulated colonic TRPV4 expression in DSS-treated mice. Intracolonic administration of the TRPV4 agonists (4alphaphorbol-12,13-didecanoate or GSK1016790A) in mice activated NF-κB and activator protein 1 (AP-1) signaling pathway, resulting in exacerbated DSS-induced colitis and even transiently increased the paracellular permeability of epithelium and blood vessel, while TRPV4-knockout mice conferred a strong resistance to the colitis (73,81). These results prove the deleterious effects of TRPV4 on mucosal inflammation.…”
Section: Trpv4mentioning
confidence: 75%
“…The agonist for TRPV4 aggravated colitis and the Trpv4-knockout alleviated colitis (73,81) TNBS-treated mice The antagonist for TRPV4 alleviated colitis…”
Section: Dss-treated Micementioning
confidence: 99%
“…Our data further suggest that TRPV4 participates in the effect of diabetes on retinal fluid accumulation. Based on the facts that (i) VEGF-mediated angiogenesis and inflammation act interdependently in the development of DME (Romero-Aroca et al, 2016), (ii) TRPV4 agonism associates with increased expression of VEGF (Chen et al, 2018) and amplifies inflammatory cascades (Alessandri-Haber et al, 2004; Alessandri-Haber et al, 2005; Alessandri-Haber et al, 2003; Matsumoto et al, 2018; Vergnolle et al, 2010), and (iii) TRPV4 antagonism and anti-angiogenic molecules synergize by activating complementary pathways to counteract the diabetes-like effects on outer BRB permeability (Arredondo Zamarripa et al, 2017), it is possible that TRPV4 blockade targets both the vasogenic and inflammatory pathways in diabetic retina (Pairet et al, 2018). Trpv4 −/− mice treated with streptozotocin are hyperglycemic, in contrast to littermates subjected to a high-fat diet (Ye et al, 2012), suggesting that the protective effect of TRPV4 inhibition against retinal edema is independent from its protective effect against insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced TRPV4 expression may be a compensatory effect in diabetes. Indeed, TRPV4 activation mediates and amplifies inflammatory responses (Alessandri-Haber et al, 2006; Alessandri-Haber et al, 2004; Alessandri-Haber et al, 2005; Alessandri-Haber et al, 2003; Matsumoto et al, 2018; Okada et al, 2016; Reiter et al, 2006; Vergnolle et al, 2010), including edema (Reiter et al, 2006; Vergnolle et al, 2010). TRPV4 blockade resolves edema in several organs (Balakrishna et al, 2014; Cheung et al, 2017; Jie et al, 2015; Lu et al, 2017; Thorneloe et al, 2012; Zhao et al, 2018) and TRPV4 selective antagonists (RN-1734 and GSK2193874) mitigate BRB breakdown in diabetic rats (Arredondo Zamarripa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In hyperglycemia and diabetes, TRPV4 activity is decreased in retinal microvascular endothelial cells 13 . The activation of TRPV4 induces inflammatory responses that result in edema 122‐125 , which can be resolved by using TRPV4 inhibitors 126,127 . TRPV4 is expressed in human corneal epithelial cells 21 , and the activation of TRPV4 results in Ca 2+ influx, which might induce regulatory volume decrease 18 .…”
Section: Trpv4 and Diabetic Retinopathymentioning
confidence: 99%